Sesquiterpenoids from the twigs and leaves of Fokienia hodginsii. Issue 7 (3rd July 2017) - Wu, Xing-De; Zhong, Wen-Wen; Ding, Lin-Fen; Tu, Wen-Chao; Yang, Hui; Gong, Xun; Peng, Li-Yan; Li, Yan; Xu, Zhong-Zhi; Zhao, Qin-Shi
Abstract: A rare carotane-type sesquiterpenoid, forkienin A (1 ), a new eudesmane-type sesquiterpenoid, forkienin B (2 ), and a new natural eudesmane-type sesquiterpenoid, forkienin C (3 ), were isolated from the twigs and leaves of Fokienia hodginsii, along with eight known sesquiterpenoids. The structures of the new compounds were elucidated on the basis of their spectroscopic analysis, including 1D and 2D NMR methods. All compounds were evaluated for cytotoxicity against HL-60, SMMC-7721, A-549, MCF-7, and SW480 cell lines.